Circular RNA circEGFR regulates tumor progression via the miR-106a-5p/DDX5 axis in colorectal cancer - Fu,Ping (2021)
Recently, an increasing number of studies have reported that dysregulation of circular RNA (circRNA) expression plays critical roles in the progression of several cancers, including colorectal cancer (CRC). However, the detailed molecular mechanisms of circRNAs involvement in CRC remain largely unknown. Here, we confirmed that the level of circEGFR was significantly increased in CRC tissues compared to matched adjacent non-tumor tissues, and a high level of circEGFR was correlated with poor clinicopathological characteristics and poor prognosis in patients with CRC. Moreover, increased circEGFR expression promoted CRC cell proliferation, migration, and invasion in vitro. Mechanistically, circEGFR acted as a ceRNA for miR-106a-5p to relieve the repressive effect of miR-106a-5p on DDX5 mRNA. Moreover, circEGFR enhanced DDX5 expression, thereby upregulating p-AKT levels. Together, these findings showed that circEGFR promoted CRC cell proliferation, migration, and invasion through the miR-106a-5p/DDX5/AKT axis, and may serve as a promising diagnostic marker and therapeutic target for CRC patients.